Procastination, internet addiction, and academic performance in Ecuadorian college students - Ramos-Galarza, Carlos (2017)
This investigation analyzed the relationship between procrastination, internet addiction, and academic performance of college students. Mixed two-phase methodology was used. In the first phase, a quantitative, non-experimental, cross-sectional and correlational design was executed. The results indicate that procrastination correlates with internet addiction (r = 0.50, p = < 0.001) and students with high academic performance have a lower incidence of procrastinating behavior t(244) = -3.60, p < 0.001 and internet addiction t(244) = -2.44, p = 0.01 compared to university students with lower academic performance. In the qualitative phase, narratives were found associated with parenting style experienced, past experiences, use of cognitive functions, use of the internet, and other categories. In conclusion, the data are discussed in relation to previous research and through the integration of quantitative and qualitative results. © 2017 Universidad Austral de Chile.